The two cines con niño : genre and the child protagonist in over fifty years of Spanish film (1955-2010) - Hogan, Erin K. (Edinburgh University Press, 2018)
This is the first genre study of child-starred cinemas from Spain. It illuminates continuities in the political use of the child protagonist in over fifty years of Spanish cinema and how the child-starred genres deploy the concept of childhood to retrospectively define the nation and its future. From Francoist popular to oppositional auteur films, and including Spanish and Latin American cinema, this monograph examines commonalities in aesthetics, narratives and genre functions. It demonstrates the impact of these narratives within Spanish film history and Francoist biopolitics, as well as providing a broader transatlantic perspective on the genre in select productions from Chile and Argentina.